EXAMINING THE FLOW EXPERIENCES OF VOCATIONAL SCHOOLS BUSINESS ADMINISTRATION STUDENTS IN THE FIELD COURSES “EXAMPLE OF GAZIANTEP” - Burak BÜYÜKOĞLU; Hazal BÜYÜKOĞLU (International Journal of Eurasia Social Sciences, 2017)
Flow theory is a subject which has been searched and developed by many scientists since the second half of 1900s and its present name was given by Csikszentmihaly. This theory contextually dwells on enjoyment that the individuals got from the activities. This study is important in terms of taking precautions, bringing innovations and offering an insight to the other researches related to other programs from the results according to the flow level of student in feld courses because flow theory focuses on the students studying business administration at vocational school. The purpose of this research is to examine the flow experiences of business administration students who study at vocational schools in Gaziantep University. In this context this study was designed based upon flow theory. This research was shaped by using screening model which is one of the quantitative research models. Business administration students studying at vocational schools in Gaziantep University form the population of the research. Simple random sampling which is one of the probability sampling was preferred to determine the sample of the research. In the direction of the analysis, the findings got from whether flow level of the business administration students on field courses differs according to the variables were interpreted in the context of flow theory.